Emerging role of high density lipoproteins as a player in the immune system - Norata, Giuseppe; Pirillo, A.; Ammirati, E.; Catapano, A. (Elsevier Ireland, 2012)
High density lipoproteins (HDL) possess a number of physiological activities. The most studied and, perhaps, better understood is the ability of HDL to promote excess cholesterol efflux from peripheral tissues and transport to the liver for excretion, a mechanism believed to confer protection against atherosclerotic cardiovascular disease. The ability of HDL to modulate cholesterol bioavailability in the lipid rafts, membrane microdomains enriched in glycosphingolipids and cholesterol, is evolutionary conserved and affects the properties of cells involved in the innate and adaptive immune response, tuning inflammatory response and antigen presentation functions in macrophages as well as B and T cell activation. Also sphingosine-1 phosphate (S1P), a major active sphingolipid carried by HDL, is of relevance in the pathogenesis of several immuno-inflammatory disorders through the modulation of macrophage and lymphocyte functions. Furthermore, HDL influence the humoral innate immunity by modulating the activation of the complement system and the expression of pentraxin 3 (PTX3). Finally, in humans, HDL levels and functions are altered in several immune-mediated disorders, such as rheumatoid arthritis, systemic lupus eritematosus, Crohn's disease and multiple sclerosis as well as during inflammatory responses.Altogether these observations suggest that the effects of HDL in immunity could be related, to either the ability of HDL to modulate cholesterol content in immune cell lipid rafts and to their role as reservoir for several biologically active substances that may impact the immune system. © 2011 Elsevier Ireland Ltd.